2001
DOI: 10.1038/nbt1001-971
|View full text |Cite
|
Sign up to set email alerts
|

Feeder-free growth of undifferentiated human embryonic stem cells

Abstract: Previous studies have shown that maintenance of undifferentiated human embryonic stem (hES) cells requires culture on mouse embryonic fibroblast (MEF) feeders. Here we demonstrate a successful feeder-free hES culture system in which undifferentiated cells can be maintained for at least 130 population doublings. In this system, hES cells are cultured on Matrigel or laminin in medium conditioned by MEF. The hES cells maintained on feeders or off feeders express integrin alpha6 and beta1, which may form a laminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
1,443
2
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,735 publications
(1,502 citation statements)
references
References 15 publications
33
1,443
2
8
Order By: Relevance
“…Each preparation typically generates about 214 mg matrix proteins from 100 g placental tissue. We tested the growth of H7 cells on FCF matrix with MEF-conditioned medium (MEF-CM), and found that about 10% of the concentration of Matrigel typically used (Xu et al, 2001) is sufficient for maintaining the self-renewing capacity of H7 hESCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each preparation typically generates about 214 mg matrix proteins from 100 g placental tissue. We tested the growth of H7 cells on FCF matrix with MEF-conditioned medium (MEF-CM), and found that about 10% of the concentration of Matrigel typically used (Xu et al, 2001) is sufficient for maintaining the self-renewing capacity of H7 hESCs.…”
Section: Resultsmentioning
confidence: 99%
“…The widely-used hESC culture system includes Matrigel (MG) as the ECM and MEF-CM (MEF-CM/MG) (Xu et al, 2001). We compared the capacity of the MEF-CM/MG culture system with our novel XF/FCF culture system for maintaining the self-renewing and pluripotent potential of hESCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid those shortcomings, several human feeder, feeder-free, recombinant laminin, and artificially-formulated defined culture systems have been developed for derivation and maintenance of hESCs, though the elements for sustaining prolonged stable undifferentiated growth in those culture systems remain unsolved [3339]. These exogenous feeder cells and molecules help maintain the long-term stable growth of undifferentiated hESCs while mask their ability to respond to differentiation inducing signals and molecules.…”
Section: Defined Platform For Well-controlled Derivation Maintenamentioning
confidence: 99%
“…Human counterparts do not have the same response to LIF [4,5], suggesting that mouse ES cells and human ES (hES) cells require different signals to maintain self-renewal and pluripotency. Recently feeder-free system has been adapted especially for culturing hES cells to eliminate the potential issues of infection and cross-species contamination [6,7]. Some feeder-free systems support the culture of undifferentiated hES cells more efficiently than others [8,9], however, porcine and bovine epiblast and ICM cells cultured on a feeder free system did not grow continuously and started senescence or differentiation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%